Lycopene and intralesional betamethasone injections in the management of oral submucous fibrosis - Dipti Singh; Mathod C Shashikanth; Neeta Misra; Sudhanshu Agrawal (Wolters Kluwer Medknow Publications, 2014)
Aims and Objectives: This study was conducted to determine the efficacy of lycopene in the management of oral submucous fibrosis (OSMF) and to compare its efficacy with intralesional betamethasone injections. Materials and Methods: Forty-four patients were divided randomly into two groups. Group I subjects were treated with 10,000 mcg of lycopene (Lyconex) daily, in two equally divided doses, for two months. Group II subjects were given intralesional injections of betamethasone. Both the groups were assessed in terms of mouth opening and burning sensation. Results: A significant improvement in mouth opening was seen in both the groups and the improvement was better in Group I. The mean improvement in mouth opening in Group I was 37.62% (12 mm) at the end of the study, which was statistically highly significant and weekly evaluation revealed that this high significance was from the third week onward, and Group II patients (only intralesional steroids) showed an average improvement of 13% (3.9 mm) at the final follow-up visit. Conclusion: Lycopene (Lyconex) is better than intralesional betamethasone injections in improving mouth opening and decreasing burning sensation.